Resistance training - the next level (Peak Performance Pub., 2006)
This workbook dissects the major current debates in resistance training, analyses the very latest scientific findings - then spells out their significance for the serious athlete. It's a rare opportunity to assess the latest thinking on resistance training for yourself, and decide how best to integrate it into your training and conditioning.